Project-Based Learning in the Merdeka Curriculum in Terms of Primary School Students' Learning Outcomes - Wulandari, Triana; Nawangsari, Nur Ainy Fardana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this research is to support and strengthen the analysis of the effectiveness of the project-based learning model for application in elementary schools. This study employs the Systematic Literature Review (SLR) method. The sources of the research articles are databases from Google Scholar and CrossRef. Each article is analyzed based on its research findings. The results of the analysis indicate that project-based learning can increase students' learning motivation, enhance problem-solving skills, improve collaboration, and develop students' skills. It can be concluded that Project-Based Learning has been proven effective in improving elementary school students' learning outcomes, not only in terms of knowledge but also skills. Furthermore, the Project-Based Learning (PjBL) model can increase students' motivation, self-confidence, tolerance, cooperation, and understanding of the material, ultimately leading to a comprehensive improvement in students' learning outcomes. This learning model will continue to be recommended for educators in the learning process in accordance with the Merdeka curriculum.